Justice and deliberation about the good life: The contribution of Latin American buen vivir social movements to the idea of justice - Séverine Deneulin (University of Bath, Centre for Development Studies (CDS), 2012)
Since the 1990s, Latin America has witnessed indigenous mobilization which contest the public policies implemented by their governments. They contend that public policy is not about following a linear development model of material accumulation, but about buen vivir or Good Living, about providing the conditions for people to live in harmony with each other and Nature. Buen vivir social movements aim at replacing the dominant cosmovision of humans above nature by another cosmovision of humans as part of nature. The paper discusses these buen vivir social movements in the context of wellbeing discourses and Sen's capability-based account of justice. It argues that buen vivir social movements testify that questions of justice cannot be separated from questions about the good life, and that the quality of relations people have with each other and with the environment, and the institutions which support these, is as important as capability outcomes for remedying unjust situations.
Keywords: 330; wellbeing; social movements; capability approach; justice; virtue ethics